1999
DOI: 10.4269/ajtmh.1999.60.469
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characteristics of recently adapted isolates of Plasmodium falciparum from Thailand.

Abstract: Abstract. The drug sensitivity characteristics and Plasmodium falciparum pfmdr1 status of five isolates of P. falciparum recently isolated from patients presenting for treatment from the Thailand/Myanmar border have been investigated. The aim of the study was to avoid the criticisms of some earlier studies by focusing on newly collected isolates from a specific geographic location. Three of the isolates studied exhibited clear resistance to chloroquine similar to that observed in the K1 Thai standard isolate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
4
8
0
Order By: Relevance
“…We found that Pgh1 is not present in the PPM or at such a low level that it could not be detected by Western blot, and that, with the exception of FAC8, all strains tested in this study expressed Pgh1 at a similar level (20-33% expression relative to FAC8) in the FV, therefore invalidating any correlation between an overexpression of Pgh1 protein and the CQR phenotype. Nevertheless, Fac8 with three copies of pfmdr1 gene had been found more resistant to mefloquine (Barnes et al 1992) than K1 with a single copy of the gene (Mungthin et al 1999). Therefore, our data showing that FAC8 displayed a higher expression of Pgh1 protein in trophozoites and FV than any other isolates tested, including the highly CQR line K1, is in agreement with the current hypothesis stating that amplification of pfmdr1/Pgh1 expression is strongly associated with mefloquine resistance (Price et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…We found that Pgh1 is not present in the PPM or at such a low level that it could not be detected by Western blot, and that, with the exception of FAC8, all strains tested in this study expressed Pgh1 at a similar level (20-33% expression relative to FAC8) in the FV, therefore invalidating any correlation between an overexpression of Pgh1 protein and the CQR phenotype. Nevertheless, Fac8 with three copies of pfmdr1 gene had been found more resistant to mefloquine (Barnes et al 1992) than K1 with a single copy of the gene (Mungthin et al 1999). Therefore, our data showing that FAC8 displayed a higher expression of Pgh1 protein in trophozoites and FV than any other isolates tested, including the highly CQR line K1, is in agreement with the current hypothesis stating that amplification of pfmdr1/Pgh1 expression is strongly associated with mefloquine resistance (Price et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Attempts to answer the question related to pfmdr1 gene amplification also have a history of conflicting results. Some studies have reported increased copy numbers with selection for mefloquine resistance (5,12), while others have not (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…No association was found between the mutation at codon 86 of the pfmdr1 gene and in vivo sensitivity to mefloquine, which is in contrast to the results of in vitro studies (8,19). Previous studies have mainly focused on the association of the pfmdr1 gene copy number and in vitro sensitivity to mefloquine (6,7,12,13,16,22,28). Few in vitro studies have examined the relationship between pfmdr1 gene mutations and mefloquine sensitivity, and the studies that have been conducted have obtained controversial results.…”
Section: Discussionmentioning
confidence: 99%